Case report: Ethylene glycol intoxication presenting as a mimic of acute stroke: a report of three cases - Héja, Máté; Oláh, László (Frontiers in Stroke, 2023)
Stroke is a major cause of death and disability presenting with acute focal neurological symptoms of vascular origin. Several other disorders may cause symptoms similar to a stroke, referred to as stroke mimics. The misdiagnosis of stroke mimics may lead to potentially harmful treatments, including thrombolysis. Intoxication is a rare, but possible, cause of stroke mimic. We present three cases of ethylene glycol poisoning presenting as an acute stroke mimic within the time window of thrombolytic therapy. Two of three patients (a 54-year-old male and a 78-year-old male) had dysarthria, nystagmus, and truncal ataxia on admission. The third patient with a history of chronic alcoholism presented after an epileptic seizure with mixed aphasia and confusion. Non-contrast cerebral computed tomography and computed tomography angiography were negative in all three cases. As stroke could not be excluded in any of the patients, thrombolysis was performed. However, after some hours, two of the three patients developed agitation, somnolence, and hyperventilation. One patient's consciousness deteriorated rapidly, and he became comatose and tetraplegic. A blood gas analysis showed acidosis in two of the three patients, and toxicological screening revealed ethylene glycol intoxication in all three cases. Due to the appropriate treatment, two of the three patients became symptom-free; however, one of the three patients died. Our cases show that ethylene glycol intoxication in its early phase may mimic acute stroke, resulting in unnecessary thrombolytic therapy. Symptoms not characteristic of a stroke, such as hyperventilation, agitation, and disturbance of consciousness, may appear later and warn of intoxication. The final diagnosis of ethylene glycol intoxication can be established by severe metabolic acidosis and toxicological screening. Close monitoring of symptoms might contribute to the early recognition of ethylene glycol intoxication and its effective treatment.